Visible Light Promoted Iron‐Catalyzed One‐Pot Synthesis of 2‐Arylimino‐2H‐Chromenes from 2‐Hydroxybenzyl Alcohols and β‐ Ketothioamides at Room Temperature. Issue 14 (22nd March 2023) - Waheed, Mohd; Alsharif, Meshari A.; Issa Alahmdi, Mohammed; Mukhtar, Sayeed; Parveen, Humaira
Abstract: An efficient, environmentally benign and one‐pot approach for the synthesis of 2‐arylimino‐2 H ‐chromenes from 2‐hydroxybenzyl alcohols and β‐ketothioamides at room temperature under visible light has been developed. The reported reaction conditions were favorable for a wide range of β‐ketothioamides afforded good to excellent yields of the respective products. The low cost and air stable Knölker iron catalyst has been employed for the dehydrogenation of 2‐hydroxybenzyl alcohols under photolysis that would usually require a higher temperature. Abstract : An efficient, environmentally benign and one‐pot approach for the synthesis of 2‐arylimino‐2 H ‐chromenes from 2‐hydroxybenzyl alcohols and β‐ketothioamides at room temperature under visible light has been developed. The reported reaction conditions were favorable for a wide range of β‐ketothioamides afforded good to excellent yields of the respective products.